Impacts of nitrogen-to-phosphorus imbalance from hybrid ocean thermal energy conversion operations on benthic communities and coastal ecosystem management - Leng, Qingxue; Mohamat Yusuff, Ferdaus; Zhang, Weiqin; Hassan, Zafri; Mohamed, Khairul Nizam; Zainordin, Nazatul Syadia (Elsevier Ltd, 2025)
Hybrid ocean thermal energy conversion (H-OTEC) power plants are an emerging source of renewable energy, necessitating research on their environmental impact to support their wider implementation. Benthic communities are highly sensitive to ammonia–nitrogen (NH₄-N) stress; however, studies on the effects of NH₄-N from OTEC operations on coastal ecosystems remain limited. This study evaluated the influence of NH₄-N stress on benthic communities by analysing seasonal variations in water and sediment parameters alongside macrobenthic and meiobenthic organism surveys. A control site in an undisturbed area was included to assess the anthropogenic impacts of H-OTEC operations and effluents from ornamental fish farms. The results indicate that NH₄-N stress significantly alters macrobenthic community structure, with U. vestiarium being the primary contributor to intergroup variation, while meiobenthic communities remain unaffected. Principal component analysis (PCA) and structural equation modelling (SEM) identified NH₄-N as a significant predictor of benthic abundance, with Chl-a concentrations increasing with NH₄-N but benthic abundance decreasing. The TN/TP ratio was below 25 and NH₄-N levels were <0.1 mg/L. The benthic abundance increased with increasing TN/TP ratio. However, when the TN/TP ratio exceeded 30, the abundance of these organisms decreased considerably. These findings suggest that monitoring TN/TP ratios could be an effective strategy for regulating ammonia stress from H-OTEC operations and thereby contributing to sustainable coastal ecosystem management.